Extraction Of Flavonoids From Butterfly Pea (Clitoria Ternatea) Flower And Their Inhibitive Effect For Corrosion Under Co2 In Low-carbon Steel - Azahar, Siti Shafiqah (2024)
The present study emphasizes the extraction of flavonoids which are quercetin and kaempferol from Butterfly blue pea (Clitoria ternatea) flower containing very strong antioxidant properties. The extracts were prepared using solvents with different polarities, namely chloroform (CTCH), ethanol (CTET), ethyl acetate (CTEA), and water (CTW). The phytochemical studies for all extracts were evaluated to screen the phenolic content, flavonoid content, reducing power assay, and tannin content as a potential source of antioxidant properties of the flower. All the extracts were then characterized using complementary analyses, including Fourier-transform infrared spectroscopy (FT-IR), Thermogravimetric analysis (TGA), Differential scanning calorimetry (DSC), Nuclear magnetic resonance (NMR) analysis (including 1H and 13C NMR). According to High-performance liquid chromatography (HPLC) and Liquid chromatography-mass spectrometry (LC-MS) analysis, the compounds found in CT extracts were identified both qualitatively and quantitatively. Electrochemical measurements, including Electrochemical impedance spectroscopy (EIS), Potentiodynamic polarization (PD), and Electrochemical noise measurement (ENM) revealed the anticorrosion performance of mild steel under a CO2 atmosphere. The performances of mild steel to prevent corrosion in 3.5% NaCl medium containing CTW and CTET extracts at different concentrations and temperatures were ascertained through electrochemical measurements.